Size matters!: body height and labor market discrimination : a cross-European analysis - Francesco Cinnirella; Joachim Winter (Center for Economic Studies and ifo Institute (CESifo), 2009)
Taller workers earn on average higher salaries. Recent research has proposed cognitive abilities and social skills as explanations for the height-wage premium. Another possible mechanism, employer discrimination, has found little support. In this paper, we provide some evidence in favor of the discrimination hypothesis. Using a cross section of 13 countries, we show that there is a consistent height-wage premium across Europe and that it is largely due to occupational sorting. We show that height has a significant effect for the occupational sorting of employed workers but not for the self-employed. We interpret this result as evidence of employer discrimination in favor of taller workers. Our results are consistent with the theoretical predictions of recent models on statistical discrimination and employer learning.
Keywords: J24; J31; J71; 330; height; wage premium; discrimination; cognitive functions; occupational sorting; Gesundheit; Arbeitsmarktdiskriminierung; Personalauswahl; Europa